Immunization status of children and its decline with age: A hospital based study of 1000 children at a teaching hospital in western Uttar Pradesh - Agrawal, Satish Chandra; Kumari, Anita (Indian Journal of Community Health, 2014)
Background: Despite the ongoing National Immunization Program, the immunization coverage in our country remains unsatisfactory, particularly in U.P.; moreover, a wide disparity is seen in the immunization coverage of children at different ages. Objectives: The present study was conducted to know the immunization status of children, up to the age of 6 years, and particularly to evaluate the same with regard to the age of the child. Methods: The present study was carried out as a cross sectional study, between September, 2012 and May, 2013 at the pediatric OPD of SRMS Institute of Medical Sciences, Bareilly. A total of 1000 children, aged up to 6 years were included. Immunization status with regard to the doses of BCG, OPV, DPT, DT and measles vaccine given at different time was assessed by interviewing parents and checking immunization cards. An endeavor was also made to know the various factors responsible for incomplete or no immunization through interviewing parents. Results: Over all, number of children with complete, partial and no immunization were 41.4%, 44.8% and 13.8% respectively. An inverse correlation exists between the age of the child and the vaccine acceptability - lesser the age, better is the coverage. Besides, a selective pattern is seen, the OPV-1 being the most preferred and DT booster (5-6 years) as the least preferred vaccine. Conclusions: There is need for improving the immunization coverage, particularly for the older children for reducing the burden of vaccine preventable diseases.